A comparative evaluation of the prevailing models for measuring sustainable performance - Khalili, Amjad; Ismail, Md Yusof; Karim, A.N. Mustafizul (Asian Research Publishing Network (ARPN), 2016)
In the twenty first century the term ‘sustainability’ is recognized unanimously as an inherent and important strategy for an organization to operate and achieve long-term competitive edge. Accordingly sustainable key performance indicators (KPI) are identified by manufacturers and introduced for adoption and application in different operational activities. However, the dimensions of the sustainability models adopted by different enterprises are quite diverse as revealed through this investigation. The organizations are found to focus on varieties of strategic aspects rather than adopting identical or uniform strategies when dealing with sustainability issues. This paper aims at reviewing the various models prevailing in the contemporary research papers along with presentation of an in-depth analysis exposing the similar and dissimilar aspects. The contribution of this review is twofold: various models for sustainable performance (SP) are critically analyzed followed by a comparative evaluation with a view to proposing a general model suitable for adoption by manufacturing enterprises. The unified model as proposed in this paper comprises of three major components related to the social, financial and environmental domains.